Personal Narratives of Illness: Redressing Madness in the Singaporean Fiction of Amanda Lee Koe - Hannah Ming-Yit Ho (Humanities, 2019)
Amanda Lee Koe’s short stories (2013) redress the limited tolerance for the mad citizen-subject, whose subjectivity is obscured, if not erased, by medical prescriptions. Official and often state-sanctioned conceptualizations of the peculiar mind are grievously justified in behavioral manifestations deemed socially unacceptable. Koe’s stories about idiosyncratic Singaporeans illustrate the way personal experiences—of memory loss, homosexual tendencies, and emotional self-expressions—are informed by, and in turn inform, the biopolitical regulation of Singaporean citizens rendered objects of biopower. In this way, her stories invite a meditation on the state, people and power. Foregrounding fractured and unorthodox characters, these stories serve to intensify individual voices articulated in personal narratives addressing affective experiences, including sadness culminating in loneliness. Furthermore, the stories attest to socially constructed norms instigating the repudiation and criminalization of sexual deviants. Significantly, they add to the “cultural apparatus„—which C.W. Mills defines as “the source of Human Variety—of styles of living and of ways to die„—by questioning the nation’s ideological imperatives, including heterosexual norms, social insistence on mono-cultural marriages and state/family-endorsed medical intervention. Offering a critique of ideological state apparatus embedded within the power structures inherent to psychopathology, Koe’s Ministry of Moral Panic challenges the established ways of viewing “Others„ who are ostensibly “mad„. Consequently, her stories mediate a broadening human experience, by calling for inclusivity amid the social rejection and insular treatment of afflicted subjects with alleged disorders.